Cartilage Lesions of the Ankle - Canata, Gian Luigi; van Dijk, C. Niek.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This booklet, published in cooperation with ISAKOS, is a concise, up-to-date guide and reference on the treatment of cartilage lesions of the ankle that will be of practical clinical value for specialists in sports medicine and sports traumatology. Different techniques and the management of various lesions are described step by step, guiding the practitioner through the entire spectrum of care from evaluation of the injury to successful recovery. Chondral and osteochondral lesions of the talus can present as a consequence of repetitive ankle injuries, causing chronic pain, recurrent swelling, and weakness and stiffness of the ankle joint. An accurate early diagnosis is required, using clinical evaluation, imaging techniques, and arthroscopy of the ankle. In acute and non-displaced chondral and osteochondral lesions, conservative treatment is the mainstay. Surgery is recommended for unstable and persistent lesions and consists in several techniques focused on regeneration of the cartilage. Returning to play is possible after testing balance and proprioception, strength, range of motion, and agility.
Current concepts and evidence-based treatment of the osteochondral lesions of the ankle -- MRI in the evaluation of osteochondral lesions -- Evolution of surgical treatment of cartilaginous lesions -- Arthroscopic debridement of osteochondral lesions of the talus -- Mosaicplasty of osteochondral lesions of the ankle -- The conservative treatment in Talar OCD: injections of PRP -- Management of the cystic osteochondral lesions -- Osteochondral ankle injuries in footballers -- Treatment of osteochondral defects of the talus in children -- Rehabilitation and return-to-sports activity after debridement and bone marrow stimulation of osteochondral talar defects.
Keywords: Orthopedics; Traumatology; Sports medicine; Surgical Orthopedics; Traumatic Surgery; Sports Medicine; Conservative Orthopedics